2008
DOI: 10.1002/jcb.21806
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic partitioning of transcription factors

Abstract: Mitosis is a highly orchestrated process involving numerous protein kinases and phosphatases. At the onset of mitosis, the chromatin condensation into metaphase chromosomes is correlated with global phosphorylation of histone H3. The bulk of transcription is silenced while many of the transcription-associated proteins, including transcription and chromatin remodeling factors, are excluded from chromatin, typically as a consequence of their phosphorylation. Components of the transcription machinery and regulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 62 publications
2
43
0
1
Order By: Relevance
“…Because transcription-related factors are excluded from mitotic chromatin, mitotic chromosomes are transcriptionally inactive [15]. In contrast, some markers for epigenetic gene control are retained during mitosis [22]. It is possible that transcription and the formation of higher order chromatin structures mediated by CTCF might result in a disadvantage to achieve accurate chromosome segregation; however, we found that a part of CTCF still interacts with mitotic chromatin as reported previously ( Fig.…”
Section: Discussionsupporting
confidence: 85%
“…Because transcription-related factors are excluded from mitotic chromatin, mitotic chromosomes are transcriptionally inactive [15]. In contrast, some markers for epigenetic gene control are retained during mitosis [22]. It is possible that transcription and the formation of higher order chromatin structures mediated by CTCF might result in a disadvantage to achieve accurate chromosome segregation; however, we found that a part of CTCF still interacts with mitotic chromatin as reported previously ( Fig.…”
Section: Discussionsupporting
confidence: 85%
“…This time frame is less consistent with rapid signal transduction events and more consistent with gradual accumulation of prodeath signals (10,35). Given that most transcription factors are displaced from mitotic chromatin, it has been postulated that the decay of mRNAs may influence cell fates during prolonged mitotic block (35,36). We predict that the differential decay of mRNAs encoding proteins that influence apoptotic cell death during mitosis leads to a gradual inclination toward death.…”
Section: Molecular Cancer Therapeuticsmentioning
confidence: 81%
“…It also indicates that RNAPII binding at the kinetochore is DNA sequence independent and does not require large tracts of repeat DNA. With few exceptions, mitosis has long been assumed to be a period of transcriptional silence, characterized by the eviction of both RNAPII and transcription factors from the bulk mitotic chromatin (25)(26)(27). In view of the dogma of mitotic gene repression, our demonstration of specific retention of RNAPII, CTDP1, and SSRP1 at the mitotic kinetochore and evidence of centromeric mitotic transcription is striking.…”
Section: Discussionmentioning
confidence: 94%